2016
DOI: 10.1126/sciadv.1601428
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-efficiency solution-processed simplified small-molecule organic light-emitting diodes using universal host materials

Abstract: Researchers achieved ultrahigh efficiency of solution-processed simplified small-molecule OLEDs that use novel universal host materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 52 publications
0
64
0
1
Order By: Relevance
“…8 The recent publication on high efficiency solution processed smallmolecule phosphorescent OLEDs reported that the devices comprising the homoleptic Ir(ppy) 3 complex had EQEs greater than 20%. 16 Given the preponderence of reports that state Ir(ppy) 3 is an isotropic emitter, the higher EQE must be due to an optical cavity effect. In this work, we have also considered the out-coupling of the light generated in the device for both the neat and blended emissive films.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The recent publication on high efficiency solution processed smallmolecule phosphorescent OLEDs reported that the devices comprising the homoleptic Ir(ppy) 3 complex had EQEs greater than 20%. 16 Given the preponderence of reports that state Ir(ppy) 3 is an isotropic emitter, the higher EQE must be due to an optical cavity effect. In this work, we have also considered the out-coupling of the light generated in the device for both the neat and blended emissive films.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent report of solution processed phosphorescent OLEDs with EQEs greater than 20%. 16 The OLEDs contain a graded hole injection layer, an emissive layer comprised of the emitter, hole and electron transport materials, with an additional electron transport layer (ETL) between the emissive layer and the cathode. Remarkably, the high EQEs were observed for both a homoleptic isotropic emitter [Ir(ppy) 3 ] as well as two heteroleptic complexes, with the results somewhat at odds with previously published work on dipole alignment for enhanced emission.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, OLEDs have been paid considerable attention to in the academic and industrial sectors due to their promising characteristics as color display, high flexibility, low driving voltage, fast response time which empower its use in a broad range of applications such as solid‐state lighting technology and next generation flat‐panel displays . Nowadays, there are two main types of organic compounds as light‐emitting materials (EM) in the OLED technology: semiconducting polymers and small molecules . The solution‐processed OLEDs based on small conjugated molecules are attracting considerable interest because they combine the advantage of both classes simplicity of fabrication and ease of purification, characteristics for conjugated polymers or for small molecules, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Good results have been obtained also via solution processing TADF small molecules and TADF exciplex hosts doped with fluorescent or phosphorescent emitters. [17][18][19][20][21][22] Here we demonstrate excellent efficiency from a simple TADF exciplex layer acting as the emitter in a device.…”
Section: Introductionmentioning
confidence: 76%